1986
DOI: 10.1515/znc-1986-0321
|View full text |Cite
|
Sign up to set email alerts
|

Notizen: Neue Pulvinsäurederivate aus Pulveroboletus- Arten (Boletales)/ New Pulvinic Acid Derivatives from Pulveroboletus Species (Boletales)

Abstract: Vulpinic acid has been isolated from sporophores of Pulveroboletus ravenelii, its first reported occurrence in a Basidiomycete. Permethyl ethers of methyl xerocomate and methyl atromentate and its corresponding monochloro derivatives are produced by P. auriflammeus of Japanese origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…9 In addition, an 80% EtOH extract of Pulveroboletus (PS-7) demonstrated antibacterial activity against Bacillus subtilis (KCTC 1028), Micrococcus luteus(KCTC1915), and Staphylococcusaureus(KCTC1621). 10 In our search for biologically active natural products from fungi, we discovered that a crude extract from P. ravenelii displayed strong activity against methicillin-resistant andsusceptible S. aureus. Analysis of this extract has resulted in the isolation of two novel compounds, 1 and 2, as well as the isolation of vulpinic acid (3) and its previously unreported polymorph.…”
mentioning
confidence: 99%
“…9 In addition, an 80% EtOH extract of Pulveroboletus (PS-7) demonstrated antibacterial activity against Bacillus subtilis (KCTC 1028), Micrococcus luteus(KCTC1915), and Staphylococcusaureus(KCTC1621). 10 In our search for biologically active natural products from fungi, we discovered that a crude extract from P. ravenelii displayed strong activity against methicillin-resistant andsusceptible S. aureus. Analysis of this extract has resulted in the isolation of two novel compounds, 1 and 2, as well as the isolation of vulpinic acid (3) and its previously unreported polymorph.…”
mentioning
confidence: 99%
“…This taxonomically rather controversial genus is characterized by the occurrence of pulvinic acid pigments, [19] often in halogenated or O-methylated form. [19,20] Our present investigation demonstrates that the pigments of B. curtisii belong to a new class of chromoalkaloids, differing profoundly from the pulvinic acids responsible for the bright color of other Pulveroboletus and many Boletus species. From these results it appears necessary to revise the taxonomic position of B. curtisii within the Boletineae.…”
Section: Discussionmentioning
confidence: 61%
“…10 P. ravenelii is also used in mushroom-based dyes to produce the colors yellow, gold, greenish yellow, orange, and olive. Previous studies demonstrated that the extract of P. ravenelii showed antibacterial activity against Bacillus subtilis, Micrococcus luteus, 11 and methicillin-susceptible and methicillin-resistant Staphylococcus aureus. 12 Chemical investigations of P. ravenelii have shown that the mushroom contains diverse phenolic compounds with unique structures including vulpinic acid, atrometic acid, isoxerocomic acid, variegatic acid, xerocomorubin and variegatorubin from Australian P. ravenelii; vulpinic acid, permethyl ethers of methyl xerocomate, methyl atrometate, ravenelone, and isoravenelone from Japanese P. ravenelii; and pulveraven A and pulveraven B from North American P. ravenelii.…”
Section: Introductionmentioning
confidence: 99%